Four single nucleotide polymorphisms in genes involved in neuronal signaling are associated with opioid use disorder in West Virginia - Kaski, BS, MD/PhD, Shane W.; Brooks, MPH, Stephan; Wen, PhD, Sijin; Haut, PhD, Marc W.; Siderovski, PhD, David P.; Berry, DO, James H.; Lander, MSW, Laura R.; Setola, PhD, Vincent (Journal of Opioid Management, 2019)
Objective: Pilot study to assess utility in opioid use disorder (OUD) of a panel of single nucleotide polymorphisms (SNPs) in genes previously related to substance use disorder (SUD) and/or phenotypes that predispose individuals to OUD/SUD. Design: Genetic association study. Setting: West Virginia University’s Chestnut Ridge Center Comprehensive Opioid Addiction Treatment (COAT) clinic for individuals diagnosed with OUD. Patients: Sixty patients 18 years of age or older with OUD undergoing medication (buprenorphine/naloxone)-assisted treatment; all 60 patients recruited contributed samples for genetic analysis. Outcome measure(s): Minor allele frequencies for SNPs. Results: Four of the 14 SNPs examined were present at frequencies that are statistically significantly different than in a demographically matched general population. Conclusions: For the purposes of testing WV individuals via genetic means for predisposition to OUD, at least four SNPs in three genes are likely to have utility in predicting susceptibility. Additional studies with larger populations will need to be conducted to confirm these results before use in a clinical setting.